PERANCANGAN USER INTERFACE E-LEARNING BERBASIS WEB - Bernard Renaldy Suteja; Agus Harjoko (Seminar Nasional Informatika (SEMNASIF), 2008)
e-Learning steadily growing and the ongoing struggle to convince the skeptics of the potential of e-Learning and online virtual classrooms, quality design is the foundation for a successful distance learning program. The design of the instruction and the design of the user interface are critical elements in providing quality education with a virtual, e-Learning model. This White Paper will focus on the design of the e-Learning user interface (UI). This paper provides examples of user interface design from e-Learning prototype.